Argument estimates of certain classes of P-Valent meromorphic functions involving certain operator - Madian, S. M. (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, by making use of subordination , we investigate some inclusion relations and argument properties of certain classes of p-valent meromorphic functions involving certain operator.